Firefly Algorithm and particle Swarm Optimization for Economic Dispatch Optimization at PLTU Tanjung Jati B - Pressa Perdana Surya Saputra (Department of Electrical Engineering ITS and FORTEI, 2018)
The definition of economics dispatch (ED), that is how to get a minimum operating cost and still meeting existing constrain. Some methods to solve this problem, that is by using Firefly Algorithm (FA) and Particle Swarm Optimization (PSO). In this research, FA and PSO method try applied to ED at PLTU Tanjung Jati B. the results show that PSO method produces a combination of generating power at a more economical and stable cost compared to the FA method. however, both are very well used in economic dispatch problems Keywords: Economic Dispatch, Firefly Algorithm (FA), PSO